Biological aspects of the beetle Delphastus davidsoni fed with whitefly eggs laid on tomato genotypes - Maria Auxiliadora de Godoy Oriani; José Djair Vendramim (Scientia Agricola, 2014)
Many plant breeding programs have incorporated plant resistance characteristics without considering how this resistance may affect the natural enemies of plant pests. We evaluated the biological aspects of Delphastus davidsoni (Gordon) fed with Bemisia tabaci B biotype eggs laid on tomato genotypes with different trichome densities and types. On LA1335 and NAV1062, the development periods were 21 days, and the larval mortality rates were 46.7 % and 28.9 %, respectively; on IAC294, the development period was 26 days, and the mortality rate 88.9 %. None of the larvae completed development when fed with whitefly eggs laid on PI134418. Most of the deaths took place in the second instar stage because the larvae became trapped in the glandular trichomes; similar results were also observed on IAC294. The adult longevity and female fecundity on LA1335 and NAV1062 were 32 and 34 days, and 61 and 78 eggs, respectively. The type IV and VI glandular trichomes present on PI134418 and IAC294 adversely affected the larval development of D. davidsoni, resulting in high mortality rates. Nevertheless, type V non-glandular trichomes, in high (NAV1062) or low (LA1335) densities, did not affect the development of the insect.